Emergence of genetic sex determination in an environmentally sex-determined animal - Wen Wei; Man Lin; Trent Bishop; Ryan Shahriari; Yue Hao; Logan Graham; Bret L. Coggins; Hannah Jee; Emma Fonseca; Swatantra Neupane; Li Wang; Sen Xu; et al. (Proceedings of the National Academy of Sciences, 2026)
The evolution of genetic sex determination (GSD) from environmental sex determination (ESD) remains a fundamental issue in evolutionary biology. However, the mechanisms driving the transition, particularly in its earliest stages, are largely unknown. Here, we report a genetic variant in the ESD species, Daphnia pulex , in which structural variations on chromosome I have suppressed recombination. This suppression appears to have facilitated the accumulation of divergent features of two chromosome I haplotypes, resulting in differentiation of the linked sex-determining gene Dfh . This process has led to the emergence of a mixed-mating system, in which sex determination is jointly regulated by genetic and environmental factors, with ongoing divergence in chromosomal structure continuing to develop between the two haplotypes at the population level. These findings suggest that processes analogous to early sex-chromosome evolution are occurring in this ESD species, offering insights into the molecular mechanisms underlying the emergence of GSD.